Degradation of dimethyl sulfoxide through fluidized-bed fenton process - Matira, Emmanuela M. (College of Engineering, University of the Philippines Diliman, 2015)
Dimethyl sulfoxide (DMSO), one of the most widely used solvents, was subjected in fluidized-bed Fenton oxidation in this study. Fenton oxidation is considered one of the cheapest advanced oxidation processes due to high availability of Fenton's reagents Fe2+ and H2O2, wherein Fe2+ catalyzes hydroxyl radical production from H2O2. Fluidized-bed Fenton process is a modified approach which is also used to address the production of large amount of iron oxide sludge in conventional Fenton process. Parametric study is included in this research using initial conditions of pH 2 to 7, 0.5 to 7.25 mM Fe2+, 5 to 87.5 mM H2O2, and 5 to 50 mM DMSO. Fluidized-bed Fenton oxidation of 5 mM DMSO using 68.97 g/L SiO2, carrier at initial conditions of pH 3, 5 mM Fe2+, and 32.5 mM HO2 resulted to 95.22% DMSO degradation, 34.38% TOC removal and 0.304 mM sulfate/ mM DMS0o production in 2 hours. The study shows that the intermediate which was most difficult to oxidize and contributed most to the residual TOC was methane sulfonate. Kinetic study was also obtained to investigate the 2 stages involved in the oxidation. Performances of fluidized-bed Fenton and conventional Fenton were also investigated.